An application for the higher order modified KdV equation by decomposition method - Kaya, Do?an (Elsevier, 2005)
The explicit solutions to the higher order modified Korteweg-de Vries equation with initial condition are calculated by using the Adomian decomposition method. To illustrate the application of this method, numerical results are obtained and compared for the third- and fourth-order generalized nonlinear Korteweg-de Vries equations. © 2004 Elsevier B.V. All rights reserved.
Keywords: Adomian decomposition method; Higher order modified nonlinear KdV equation; Solitary wave solution